The Effect of Acupressure Therapy on Blood Pressure in Hypertensive Patients at Dawan Usadha Nurse Practitioner - Kresna Aditya I Gusti Ngurah; Candrawati Sang Ayu Ketut; Desak Made Ari Dwi Jayanti; Theresia Anita Pramesti (Yayasan Lentera Mitra Lestari, 2026)
Background: Hypertension is one of the most prevalent non-communicable diseases and a major risk factor for cardiovascular disorders; therefore, its management should not rely solely on pharmacological therapy but also needs to be supported by safe, effective, and easily applicable non-pharmacological interventions in nursing practice, one of which is acupressure therapy. Objective: This study aimed to determine the effect of acupressure therapy on blood pressure among patients with hypertension at Dawan Usadha Independent Nurse Practice. Method: This study employed a pre-experimental one-group pretest–posttest design involving 20 hypertensive patients selected using purposive sampling. The sample size was determined based on the number of hypertensive patients who met the inclusion criteria during the study period. Acupressure therapy was administered at LI11, LI4, LR3, SP6, and GB20 points twice weekly for four weeks. Blood pressure was measured before and after intervention using a calibrated digital sphygmomanometer. Data were analyzed using the Wilcoxon Signed Rank Test. Result: The results demonstrated a reduction in blood pressure following the acupressure intervention, in which the mean systolic blood pressure decreased from 150.30 mmHg to 142.30 mmHg, with a mean difference of 8.00 mmHg and a p-value of <0.001, while the mean diastolic blood pressure decreased from 89.40 mmHg to 85.60 mmHg, with a mean difference of 3.80 mmHg and a p-value of 0.002. Conclusion: Acupressure therapy significantly reduced blood pressure among hypertensive patients and may serve as an effective complementary non-pharmacological intervention in hypertension management.